Public Relations and Sustainable Development in Question in French Academic Works - Bouzon, Arlette (2011)
The needs to inform and convince are millenniums and part of any organized life. Due to the very nature of its activities in the economic and social sphere, and because the “Know-How” is no longer possible without the “Make-Known”, the organization (generally companies, associations, the public sector) has turned itself into a communication agent. In this difficult and uncertain present context, communication appears to be essential in the process of gradually becoming better aware of sustainable development, mainly when it comes to how the corresponding reports are devised. It seems to be an especially delicate matter inherently presenting a risk for the organization. Should one remain silent? Or should one speak out? And if so, how should one put things and how far should the level of uncertainty be revealed? So, communication around Sustainable Development constitutes an emerging problem area whose significance goes well beyond the usual speculation related to crisis communication which latter only addresses one of its facets. In the present article, works covering organizational communication are reviewed, focusing on the existing scientific literature on the subject. We shall thus be led to re-direct our attention to the conceptual and theoretical origins of the communication and organization couple, taking a special interest in the underlying epistemological foundations.